(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective (s): The aim of this study was to explore the outcome of abdominal sacrocolpopexy for the correction of post hysterectomy vaginal vault prolapse. Materials and Methods: This prospective study was done over the period of five years from 2011 to 2015 where twenty patients of vault prolapse were subjected to abdominal sacrocolpopexy. Procedure was completed by securing the vaginal apex to the anterior longitudinal ligament of sacrum using synthetic mesh. Intra and postoperative complications and patients satisfaction was assessed. Results: No post-operative serious complications were reported during follow up period. The vaginal vault was well supported in all patients with no recurrent vault prolapse. One patient had mild asymptomatic rectocele. No mesh complication was found during the follow up period. Conclusion: The abdominal sacrocolpopexy achieves excellent correction of post hysterectomy vaginal vault prolapse with minimal morbidity. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(2) : 90-93